Optimization of factors affecting biogas production from POME - M. Shahidul, Islam; Malcolm, M. L.; Eugene, J. J.; Mamunur, R. (Publications International Lahore, Pakistan, 2018)
This paper documents a study on biogas production from palm oil mill effluent (POME) by anaerobic digestion. The study aims to optimize biogas production from POME by employing the effect of optimal level of inputs and to develop an appropriate model to predict its processes. In this study, the continuous-stirred reactor was used to treat POME, where the inputs monitored, were Organic Loading rate, Hydraulic Retention Time and Sludge Retention Time. Waste fruit-based inoculum and NaOH were used to adjust Carbon to Nitrogen ratio and pH value. The novelty of this research was to harness the biogas production potential of hazardous POME in line with the waste to energy [WtE] concept. In order to come up with credible research design and analysis, DOE software was used. The findings in surface response diagrams of DOE manifested that the optimum inputs for maximum biogas production of 3.8L.d-1 are; 5g L-1 d -1 for OLR, 28 for C/N and 6.5 days for HRT. The validation results of the developed model affirm that the overall error in model prediction is 1.51 percent with respect to actual outputs from the anaerobic reactor. Thus, this study justifies that further research on POME should be done at economic scale CSTR reactor using the optimum value of inputs for maximum productivity of biogas in order to contribute to achieving economic and environmental sustainability.